8.145. Rozwiąż równanie: x³ 3 3x ^ 3 – 7x ^ 2 – 7x + 3 = 0; x ^ 4 – 3x ^ 3 + 4x ^ 2 = 12x e) x ^ 3 – 8 = (x – 2)(x + 6) 169 x ^ 5 + 1 = 0 f) x x ^ 8 + 2x ^ 4 + 1 = 0 b) (x ^ 2 – 4x + 1)(x ^ 2 + 5) * (8 – x ^ 3) = 0 d) (9x ^ 2 – 25)(125x ^ 3 + 216) = 0 f) ( (x ^ 4 – 256)(3x ^ 2 – 6) * (x ^ 3 + 27) = 0 b) – 5(x ^ 2 – 3x) = x ^ 2 * (3x – x ^ 2) d) 4x ^ 2 * (3 – 2x) + 4x ^ 2 = 6x f) 9x ^ 2 * (x + 2) + 6x * (x + 2) = – x – 2 b) 8x ^ 5 – 32x ^ 3 – x ^ 2 + 4 = 0 d) x ^ 5 – x ^ 3 – 125x ^ 2 + 125 = 0 f) – 27x ^ 5 + 54x ^ 3 – x ^ 2 + 2 = 0 b) 3x ^ 5 – 2x ^ 4 + 2 – 3x = 0 d) x ^ 4 + 4x ^ 3 = 5x ^ 2 + 20x f) x ^ 5 – 2x ^ 3 = (2 – x ^ 2) * x ^ 2

8.145. Rozwiąż równanie: x³ 3 3x ^ 3 – 7x ^ 2 – 7x + 3 = 0; x ^ 4 – 3x ^ 3 + 4x ^ 2 = 12x e) x ^ 3 – 8 = (x – 2)(x + 6) 169 x ^ 5 + 1 = 0 f) x x ^ 8 + 2x ^ 4 + 1 = 0 b) (x ^ 2 – 4x + 1)(x ^ 2 + 5) * (8 – x ^ 3) = 0 d) (9x ^ 2 – 25)(125x ^ 3 + 216) = 0 f) ( (x ^ 4 – 256)(3x ^ 2 – 6) * (x ^ 3 + 27) = 0 b) – 5(x ^ 2 – 3x) = x ^ 2 * (3x – x ^ 2) d) 4x ^ 2 * (3 – 2x) + 4x ^ 2 = 6x f) 9x ^ 2 * (x + 2) + 6x * (x + 2) = – x – 2 b) 8x ^ 5 – 32x ^ 3 – x ^ 2 + 4 = 0 d) x ^ 5 – x ^ 3 – 125x ^ 2 + 125 = 0 f) – 27x ^ 5 + 54x ^ 3 – x ^ 2 + 2 = 0 b) 3x ^ 5 – 2x ^ 4 + 2 – 3x = 0 d) x ^ 4 + 4x ^ 3 = 5x ^ 2 + 20x f) x ^ 5 – 2x ^ 3 = (2 – x ^ 2) * x ^ 2